PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA PADA MATERI ARITMATIKA SOSIAL DI SMP NEGERI 2 LIMBOTO - Tristanti Anggraini Usman; Kartin Usman; Siti Zakiyah; Abdul Wahab Abdullah; Abas Kaluku; Franky Alfrits Oroh (Irfani, 2021)
This research aims to determine the effect of using the Problem Based Learning Model on students’ mathematical problem-solving ability, which is higher than using a direct learning model on Social Arithmetic topics. This research was conducted at SMP Negeri 2 Limboto with the experimental method involving 2 classes as the experimental class and the control class with the number of students in each class, namely 20 students as the research sample selected using cluster random sampling technique. The research design used was a pretest-posttest control group design and the data collection technique used was giving a problem-solving ability test in the form of an essay. Inferential analysis in this study using the ANCOVA test. The results of this study indicate that the mathematical problem-solving ability of students who are taught using the Problem Based Learning Model is higher than the mathematical problem-solving abilities of students who are taught using the Direct Learning Model on Social Arithmetic material.